A Comparative Analysis between Sequential Boost and Simultaneous Integrated Boost Volumetric Modulated Arc Therapy in Head and Neck Cancer Patients - Sharma, Divya; Kumar, H S; Sharma, Neeti; Mohata, Shweta (Asian Pacific Journal of Cancer Care, 2025)
Background: In head and neck cancer radical VMAT can be delivered by two techniques: Sequential Boost (SEQ) and Simultaneous Integrated Boost (SIB). Our aim is to compare SEQ and SIB planning techniques of VMAT in patients of Head and Neck Squamous Cell Carcinoma (HNSCC) in terms of acute toxicities and disease response. Materials and Methods: A prospective randomized comparative study was conducted at ATRCTRI, S.P. Medical college Bikaner from January 2023 to December 2024. A total of 60 patients of locally advanced HNSCC of stage II- IVA planned for radical chemoradiation were enrolled into two arms equally between SEQ-VMAT and SIB-VMAT. Concurrent Chemotherapy was given with weekly cisplatin (40 mg/m2). Acute toxicity evaluation was done at end of the treatment. Response evaluation was done as per Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1 at the 3- and 6-months post treatment. Results: Acute toxicities at the end of the treatment, mucositis, dysphagia, and xerostomia are comparable in both arms, SIB has statistically significant dermatitis. At 3 months of follow up, 76 % patients in SIB arm and 70% patients in SEQ arms had complete response, 5 in SIB and 6 in SEQ patients had partial response, 2 in SIB arm and 3 patients in SEQ arm had progressive disease. At 6 months of follow up, all the patients in both arms who achieved PR by 3rd month had stable disease and 1 patient in SIB arm who had PD achieved PR. All responses were statistically nonsignificant. Conclusion: SIB-VMAT and SEQ-VMAT are comparable in terms of overall response. Whereas SEQ-VMAT appears better in terms of acute toxicities but SIB-VMAT was more convenient as it has 6 weeks treatment compare to SEQ (7-week treatment) and no re-planning is required in SIB arm.